Diffusion property and functional connectivity of superior longitudinal fasciculus underpin human metacognition - Zheng, Yunxuan; Wang, Danni; Ye, Qun; Zou, Futing; Li, Yao; Kwok, Sze Chai (Neuropsychologia, 2021)
Metacognition as the capacity of monitoring one's own cognition operates across domains. Here, we addressed whether metacognition in different cognitive domains rely on common or distinct neural substrates with combined diffusion tensor imaging (DTI) and functional magnetic resonance imaging (fMRI) techniques. After acquiring DTI and resting-state fMRI data, we asked participants to perform a temporal-order memory task and a perceptual discrimination task, followed by trial-specific confidence judgments. DTI analysis revealed that the structural integrity (indexed by fractional anisotropy) in the anterior portion of right superior longitudinal fasciculus (SLF) was associated with both perceptual and mnemonic metacognitive abilities. Using perturbed mnemonic metacognitive scores produced by inhibiting the precuneus using TMS, the mnemonic metacognition scores did not correlate with individuals' SLF structural integrity anymore, revealing the relevance of this tract in memory metacognition. To further verify the involvement of several cortical regions connected by SLF, we took the TMS-targeted precuneus region as a seed in a functional connectivity analysis and found the functional connectivity between precuneus and two SLF-connected regions (inferior parietal cortex and precentral gyrus) mediated mnemonic metacognition performance. These results illustrate the importance of SLF and a putative white-matter grey-matter circuitry that supports human metacognition. •Superior longitudinal fasciculus (SLF) integrity associated with metacognition.•Metamemory and SLF integrity correlation reduced by transient precuneus lesion.•Metamemory increases with precuneal-frontal-IPL functional connectivity.